Ukhuwah Islamiyah, Wathaniyah, and Basyariyah in the Qur'an - Salehuddin Mattawang; Sulaeman Sulaeman; Abdurrahman Abdurrahman; Irfan Irfan; Muhammad Amri (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2026)
Abstract This study examines the concept of ukhuwah (brotherhood) in the Qur'an through a thematic (maudhui) approach, encompassing three dimensions: ukhuwah islamiyah (brotherhood in faith), ukhuwah wathaniyah (brotherhood in nationality), and ukhuwah basyariyah (universal human brotherhood). These three dimensions are reflected against the local wisdom of Marimoi Ngone Futuru as the foundational philosophy of fraternity in North Maluku. Employing Al-Farmawi's thematic exegetical method with an analytical-integrative approach, this study finds that all three Qur'anic dimensions of ukhuwah share significant common ground with the philosophy of Marimoi Ngone Futuru, manifested in the traditions of Hibua Lamo, Pela Gandong, and communal cooperation (bari). The two are complementary: the Qur'an provides the theological-normative foundation, while Marimoi Ngone Futuru serves as an authentic medium of cultural contextualization. This study affirms that local wisdom and Qur'anic values can synergize to build sustainable social cohesion in North Maluku. Abstrak Penelitian ini mengkaji konsep ukhuwah dalam Al-Qur'an secara tematik (maudhui) yang meliputi tiga dimensi: ukhuwah islamiyah, wathaniyah, dan basyariyah, serta merefleksikannya dengan nilai persaudaraan Marimoi Ngone Futuru sebagai kearifan lokal Maluku Utara. Dengan menggunakan metode tafsir tematik Al-Farmawi dan pendekatan analitik-integratif, penelitian ini menemukan bahwa ketiga dimensi ukhuwah Qur'ani memiliki titik temu yang signifikan dengan filosofi Marimoi Ngone Futuru yang termanifestasi dalam tradisi Hibua Lamo, Pela Gandong, dan gotong royong (bari). Keduanya bersinergi secara komplementer: Al-Qur'an memberikan landasan teologis-normatif, sementara Marimoi Ngone Futuru menjadi medium kontekstualisasi kultural yang autentik. Penelitian ini menegaskan bahwa kearifan lokal dan nilai Qur'ani tidak bertentangan, melainkan dapat bersinergi dalam membangun kohesi sosial berkelanjutan di Maluku Utara.